THE EFFECT OF FIRM SPECIFIC ADVANTAGES AND MONITORING MECHANISM TO FOREIGN SUBSIDIARIES PERFORMANCE - Jabin, M. Ibnu Fajril; Sutrisno, -; Nurkholis, Nurkholis (Accounting Department,, 2015)
The purpose of this study is to examine the effect of firm-specific advantages and monitoring mechanisms on the performance of foreign subsidiaries in Indonesia. Firm-specific advantages refer to marketing ability, management ability, and firm size. Monitoring mechanism refer to independent commisioner and financial leverage. This study using purposive sampling in collecting the data. The sample in this study consist of manufacturing company that is listing on the Indonesian Stock Exchange in 2012. The results indicate that the management expertise and financial leverage significant effect on the performance of foreign subsidiaries. Business strategy that run the company failed to moderate the relationship between firm -specific advantages and monitoring mechanisms on the performance of foreign subsidiaries. Keywords: Firm-Specific Advantages, Monitoring Mechanism, Bussiness Strategy, Firm Performance, Foreign Subsidiary